2020
DOI: 10.1136/ijgc-2020-001682
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, prevalence, and factors associated with lymphedema after treatment for cervical cancer: a systematic review

Abstract: BackgroundLower limb lymphedema is a frequent and debilitating complication after cervical cancer treatment.ObjectiveTo evaluate the incidence and prevalence of lymphedema after treatment for cervical cancer and evaluate the factors associated with this outcome.MethodsThe study was performed according to the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines and was registered in the International Prospective Register of Systematic Reviews (PROSPERO). Eligible studies were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…We found lower extremity lymphoedema to be associated with RHRT in multiple quality of life studies [21,24,25]. This is in line with a recent review, that reported adjuvant radiotherapy and (the extent of) lymphadenectomy as main risk factors for developing lower extremity lymphoedema after cervical cancer treatment [39]. The authors also showed that the incidence of lower extremity lymphoedema seems to increase with follow-up.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found lower extremity lymphoedema to be associated with RHRT in multiple quality of life studies [21,24,25]. This is in line with a recent review, that reported adjuvant radiotherapy and (the extent of) lymphadenectomy as main risk factors for developing lower extremity lymphoedema after cervical cancer treatment [39]. The authors also showed that the incidence of lower extremity lymphoedema seems to increase with follow-up.…”
Section: Discussionsupporting
confidence: 89%
“…Correspondingly, in the present review, distress from lower extremity lymphoedema was reported in studies with varying follow-up periods. Ferreira Bona et al [39] confirmed our finding that lower extremity lymphoedema occurs less often after PRT than after RHRT. As the benefit of lymphadenectomy in patients treated with PRT for intraoperatively diagnosed lymph node positive cervical cancer has shown to be debatable [19], clinicians should take into account that chances of developing lymphoedema increase with the extent of lymph node dissection.…”
Section: Discussionsupporting
confidence: 88%
“…Lower lymphadenoma is one of the most common complication effecting the quality of life of many patients. A systematic review including 23 articles, revealed the factors associated with lymphedema after treatment of cervical cancer [20]. The extension of lymphadenectomy and number of RLN increase the risk of lymphedema [20].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review including 23 articles, revealed the factors associated with lymphedema after treatment of cervical cancer [20]. The extension of lymphadenectomy and number of RLN increase the risk of lymphedema [20]. Sentinel lymph node (SNL) mapping might be a promising option to minimize the risk of lower limb lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 58.7% of the ARH patients and 47.1% of the MIRH patients received postoperative adjuvant therapy in the SUCCOR study [29]. The combination of surgery and radiotherapy increases morbidity, especially from lymphoedema [30], and should therefore be avoided when possible.…”
Section: Comparisons With Previous Studiesmentioning
confidence: 99%